Creation of cell micropatterns using a newly developed gel micromachining technique. (26th July 2016) - Nakashima, Yuta; Yamamoto, Yusuke; Hikichi, Yuki; Nakanishi, Yoshitaka
Abstract: Creation of cell micropatterns comprising heterogeneous cell populations is an important technique for tissue engineering, medical transplantation, drug discovery, and regenerative medicine. This paper presents a novel gel patterning technique similar to general micromachining for creating cell micropatterns using alginate gel to inhibit cell adhesion. The alginate thin-film micropattern was formed on a glass plate by photolithography and wet etching. Cell micropatterns were subsequently created along the alginate micropattern on the glass plate. This technique permits the creation of cell micropatterns with arbitrary geometry because hydrogel materials promoting or inhibiting cell adhesion can be patterned precisely. Moreover, this technique permits processing of the culture surface during cultivation because none of the materials used such as hydrogels and hydrogel-etching solutions exhibit cytotoxicity. A cell micropattern comprising different cell types was successfully created using the presented technique. This technique will be conducive to further improvement of the fabrication of artificial tissues formed by heterogeneous cells.